2014
DOI: 10.1016/j.atherosclerosis.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular disease across the spectrum of older age: The Cardiovascular Health Study

Abstract: Objective The associations of some risk factors with cardiovascular disease (CVD) are attenuated in older age; whereas others appear robust. The present study aimed to compare CVD risk factors across older age. Methods Participants (n=4,883) in the Cardiovascular Health Study free of prevalent CVD, were stratified into three age groups: 65–74, 75–84, 85+ years. Traditional risk factors included systolic blood pressure (BP), LDL-cholesterol, HDL-cholesterol, obesity, and diabetes. Novel risk factors included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 40 publications
4
42
0
1
Order By: Relevance
“…This finding supports the argument that the associations between traditional risk factors and stroke are attenuated with advancing age 6, 7) . There are two possible explanations for this finding 6) . First, survivors with risk factors in the old-old age group may differ through selection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding supports the argument that the associations between traditional risk factors and stroke are attenuated with advancing age 6, 7) . There are two possible explanations for this finding 6) . First, survivors with risk factors in the old-old age group may differ through selection.…”
Section: Discussionsupporting
confidence: 87%
“…Because the incidence of stroke rises markedly with age 2) , older people may receive more absolute benefits from the prevention of stroke than younger people. A few prospective cohort studies have shown significant associations between traditional risk factors and stroke among older people 35) , but these associations become progressively weaker with increasing age 6, 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study demonstrates that the acylcarnitine concentration-lowering compound methyl-GBB attenuates the development of atherosclerosis by inhibiting activation of immune cells, decreasing their secretion of pro-inflammatory cytokines and possibly by reducing deleterious effects of acylcarnitines on the vascular endothelium. Postprandial hypertriglyceridaemia and elevated LDL levels are risk factors for the development of atherosclerosis [5,21]. Methyl-GBB treatment induced decrease in TG concentration, thus, the decrease of TG concentration could contribute the attenuation of development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our work, in the Odden et al study, diabetes mellitus eliminates the protective effect in women, thereby increasing coronary heart disease risk in this group. Furthermore, it was demonstrated that diabetic females had a lower treatment for modifiable CVRF in proportion to males [14] . We have not found any differences between both populations considering the number of affected vessels nor the location of injuries with the exception of those detected in the LMA which were more frequent among the diabetic population.…”
Section: Discussionmentioning
confidence: 99%